HUBUNGAN FAD DIETS, CITRA TUBUH, STRES, TEKANAN TEMAN SEBATA DENGAN GANGGUAN MAKAN PADA REMAJA PUTRI USIA 16-18 TAHUN: Hubungan Fad Diet, Citra Tubuh, Stres, Tekanan Teman Sebaya dengan Gangguan Makan pada Remaja Putri Usia 16-18 Tahun - Puspita, Berliana; Lestari, Anik; Andayani, Tri Rejeki (Amerta Nutrition, 2024)
Background: Girls experience increases in body fat and weight from puberty through late adolescence. In order to achieve their ideal body weight, young women as a consequence changed their eating habits, exercised, took care of their bodies, and used diet pills among other things. Eating disorders are caused by this practice. Persistent eating disorders can result in illness among those affected. Objectives: The aim of this research was to examine how eating disorders in female teenagers are related to fad diets, body image, stress, and peer pressure. Methods: An observational research methodology employing a cross-sectional analytic polling design was utilized. Purposive sampling Simple random sampling was used to collect data from a total of 111 individuals. From July to August 2022, the study was carried out in several secondary schools in Malang City. Results: Research results revealed a significant connection between binge eating disorder and body image (p=0.002), stress (p=0.001), and social pressure (p=0.000). However, there was no observed association between fad diets and binge eating disorder. Eating disorders exhibited a multivariate relationship with fad dieting, body image, stress, and peer pressure, as evidenced by a Nagelkerke R square value of 0.595. Conclusions: There is a correlation between eating disorders and fad diets, as well as stress, peer pressure, and body image.